Islamisme dan Post-Islamisme Kyai: Memantapkan Nalar dan Sikap Islamisme Ala Intelektual Pesantren - Atmari Atmari (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper is more inclined to the side of conception: how exactly Islamism and Post-Islamism is firmly held by the kyai as intellectual pesantren, not the only pesantren leader. Islamism and Post-Islamism are very consistent, transmitted, and transmitted to all communities around the pesantren, or exemplified and taught to the students in the pesantren environment. This paper also wants to highlight and describe some views of pesantren leaders who have works / ideas that are disseminated, rewritten, and can be read as intellectual products. This paper will be approached using phenomenological theory and symbolic interactionism, and the ethical procedures contained in qualitative research. As a result, based on this series of research, it is found that there is a consistent and changing pattern in the context of pesantren Islamic thought. The consistent thing is how the nationalist-religious epistemology construct that is held tehuh as the derivative legacy of the previous kyai. While that is changing is the way and the process of packaging a more modern pesantren-based scholarship study.